2005
DOI: 10.1002/bjs.4843
|View full text |Cite
|
Sign up to set email alerts
|

Prospective evaluation of the impact of [18F]fluoro-2-deoxy-d-glucose positron emission tomography of resectable colorectal liver metastases

Abstract: Whole-body FDG-PET may identify unrecognized extrahepatic metastases in patients with potentially resectable liver metastases imaged by CT. However, additional information provided by PET is not as reliable as suggested by earlier retrospective studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
71
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(78 citation statements)
references
References 37 publications
5
71
0
2
Order By: Relevance
“…CT has previously been established as a way to evaluate response to chemotherapy treatment in solid tumors as defined by the Response Evaluation Criteria in Solid Tumors (RECIST) criteria [25]. FDG-PET, due to its superior sensitivity in detecting extrahepatic disease, is extremely useful in reducing the number of futile operative procedures performed in patients with otherwise occult metastatic disease [26][27][28][29]. The utility of this preoperative study was also shown by Strasberg et al [30] to lessen tumor recurrence in a chemo-naïve patient cohort undergoing hepatic resection for colorectal metastases.…”
Section: Discussionmentioning
confidence: 99%
“…CT has previously been established as a way to evaluate response to chemotherapy treatment in solid tumors as defined by the Response Evaluation Criteria in Solid Tumors (RECIST) criteria [25]. FDG-PET, due to its superior sensitivity in detecting extrahepatic disease, is extremely useful in reducing the number of futile operative procedures performed in patients with otherwise occult metastatic disease [26][27][28][29]. The utility of this preoperative study was also shown by Strasberg et al [30] to lessen tumor recurrence in a chemo-naïve patient cohort undergoing hepatic resection for colorectal metastases.…”
Section: Discussionmentioning
confidence: 99%
“…18 Fluorodeoxyglucose positron emission tomography (FDG-PET) detects changes in glucose uptake and metabolism, and also provides information about the location of a cancer within tissues. It is now considered to be a sensitive and accurate technique, and several studies have suggested that it should be carried out before resection of liver metastases from CRC van der Hiel et al, 2001;Fernandez et al, 2004;Truant et al, 2005;Wiering et al, 2005;Khan et al, 2006).…”
mentioning
confidence: 99%
“…Compared to CT, PET is superior for the detection of extrahepatic metastases [29,32]. In a prospective trial, PET sensitivity was equivalent to CT for detection of hepatic metastasis but was superior for extrahepatic sites (63 vs. 25 %) [32]. In this study, PET identified 5 additional patients with extrahepatic disease but also falsely upstaged 3 patients out of a total of 59 [32].…”
Section: Positron Emission Tomographymentioning
confidence: 58%
“…Compared to CT, PET is superior for the detection of extrahepatic metastases [29,32]. In a prospective trial, PET sensitivity was equivalent to CT for detection of hepatic metastasis but was superior for extrahepatic sites (63 vs. 25 %) [32].…”
Section: Positron Emission Tomographymentioning
confidence: 96%
See 1 more Smart Citation